In situ atomic-scale imaging of the metal/oxide interfacial transformation - Zou, Lianfeng; Li, Jonathan; Zakharov, Dmitri; Stach, Eric A.; Zhou, Guangwen (Nature communications, 2017)
Directly probing structure dynamics at metal/oxide interfaces has been a major challenge due to their buried nature. Using environmental transmission electron microscopy, here we report observations of the in-place formation of Cu 2 O/Cu interfaces via the oxidation of Cu, and subsequently probe the atomic mechanisms by which interfacial transformation and grain rotation occur at the interfaces during reduction in an H 2 gas environment. The Cu 2 O→Cu transformation is observed to occur initially along the Cu 2 O/Cu interface in a layer-by-layer manner. The accumulation of oxygen vacancies at the Cu 2 O/Cu interface drives the collapse of the Cu 2 O lattice near the interface region, which results in a tilted Cu 2 O/Cu interface with concomitant Cu 2 O island rotation. These results provide unprecedented microscopic detail regarding the redox reactions of supported oxides, which differs fundamentally from the reduction of bulk or isolated oxides that requires the formation of new interfaces between the parent oxide and the reduced phase. Metal/oxide interfaces play an important role in heterogeneous catalysis and redox reactions, but their buried nature makes them difficult to study. Here, the authors use environmental transmission electron microscopy to probe the atomic-level transformations at Cu 2 O/Cu interfaces as they undergo redox reactions.